Mitigating El Niño impacts on hydro-energy vulnerability through identifying resilient run-of-river small hydropower sites - Chandni Thakur; Claudia Teutschbein; KS Kasiviswanathan; Bankaru-Swamy Soundharajan (Journal of Hydrology: Regional Studies, 2024)
Study region: The Godavari River basin (GRB), situated between the geographical coordinates of 73°21′ E to 83°09′ E and 16°07′ N to 22°50′ N, India Study focus: We developed an integrated framework combining the variable infiltration capacity (VIC) model and geospatial tools to identify potential sites for run-of-river small hydropower plants (RoR-SHP) capable of meeting the GRB's energy demands during El Niño events. This study utilized long-term (1951–2020) daily streamflow data, simulated with the VIC model for design discharge computation at 30%, 75%, and 90% flow dependability and provided a thorough assessment of the potential of RoR-SHP in the GRB. New hydrological insights for the region: The analysis revealed the GRB's potential for RoR-SHP development, identifying 226 potential sites based on the head along the river, with a combined power and annual energy generation estimate of 92 MW and 0.4 TWh/yr, respectively, at 90% flow dependability. After meticulous screening, 11 potential sites based on the head and the power potential demonstrated a decline of 46.03%, 37.97%, and 17.77% in annual energy at 30%, 75%, and 90% flow dependability, respectively, leaving nine sites maintaining the firm power (90% flow dependability) even during El Niño years. Our findings underscore the increased risk of power shortages during El Niño years and emphasize the need to develop appropriate strategies to cope with the risks associated with El Niño events.